UPAYA KOMUNIKASI PIMPINAN PT. BFI FINANCE CABANG BAGAN BATU DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN SUMBER DAYA MANUSIA - Muhammad Nuriadi; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The success of an institution's goals cannot be separated from the role of a leader. In delivering messages, the leader gives information to the super visor employee (SPV) while the information is not well understood by the super visor (SPV) which causes the information to be conveyed to the employees underneath, so the delivery of the message cannot go as well as what is desired leader. The purpose of this study was to determine the vertical, horizontal and diagonal communication that occurred at PT.BFI Finance Bagan Batu Branch in increasing employee productivity in human resources (HR). This study uses qualitative research methods with the concept of leadership. Subjects were selected using purposive sampling technique. This study uses data collection techniques of observation, interviews and research documentation.The results showed that vertical communication by the leadership can be done at any time, either directly or indirectly according to the situation and conditions. In the leadership of implementing communication on two levels, namely communication between leaders to employees of the super visor (SPV) and communication of leadership to employees of the staff section. In the communication carried out by the leadership, the way to consider employees as partners is more open discussion to exchange ideas about work issues. Horizontal communication is horizontal communication with the same position. Communication that occurs in the company to the leadership also conducts this communication not within one company, but with the head of another branch company BFI is used to formulate a strategy of what will be done to improve the performance of employees in the company. In addition to the leadership, employees and staff also conduct this communication, the communication that they do with the same position is useful to facilitate problem solving and mutual care with problems faced by other employees in order to achieve common goals at the company PT.BFI Finance Bagan Batu Branch. Furthermore diagonal communication is communication that crosses one another. In this communication it should be applicable to any company, but in contrast to PT. BFI Finance Bagan Batu Branch does not often use this communication which will result in misinformation of information provided and will also lead to new problems that arise.